2014
DOI: 10.1155/2014/407385
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofLegionellaspp. from Domestic Water in the Prefecture of Arta, Greece

Abstract: The aim of this research was the isolation of Legionella spp. from domestic water supply networks in the Prefecture of Arta. A total of 100 water samples, from 25 houses, were collected. Half of the samples concerned the cold water and half the hot water supply. Purpose was to detect colonization of the water networks with Legionella spp. >500 cfu/L by using the method of filtration (ISO 11731). Out of 100 samples, 6 samples from 3 houses were positive for Legionella spp. Legionella pneumophila serogroup 2–14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
3
9
1
Order By: Relevance
“…Schools group demonstrate a rate of 39% of Legionella spp prevalence in air conditioners, which may become a threat if not controlled. Results of this study revealed 36.2% Legionella positive growth for the houses, which is a higher result when compared with the results obtained by Dimitriadi and Velonakis [13], whom detected Legionella species from houses domestic water in Greece in only 17% from a total of 100 collected samples. Our results was almost similar to that of a previous study done by Burak and Zeybek [6], who collected 122 samples from hot water and swabs from the showers in 61 houses in Istanbul, who isolated Legionella pneumophila from 13 (21.3%) of the houses.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Schools group demonstrate a rate of 39% of Legionella spp prevalence in air conditioners, which may become a threat if not controlled. Results of this study revealed 36.2% Legionella positive growth for the houses, which is a higher result when compared with the results obtained by Dimitriadi and Velonakis [13], whom detected Legionella species from houses domestic water in Greece in only 17% from a total of 100 collected samples. Our results was almost similar to that of a previous study done by Burak and Zeybek [6], who collected 122 samples from hot water and swabs from the showers in 61 houses in Istanbul, who isolated Legionella pneumophila from 13 (21.3%) of the houses.…”
Section: Discussioncontrasting
confidence: 75%
“…A total of 525 water samples were collected from water reservoirs of air conditioning systems in the three main cities of Khartoum State (Khartoum, Omdurman and Khartoum North) in the period between March -October, 2012, 2013, 2014, 2015 and 2016. The premises from which the samples were collected were divided into five categories: universities, schools, hospitals, offices and houses (35 samples for each category in the three cities, with a total of 175 samples for each city).…”
mentioning
confidence: 99%
“…Percentages of Legionella-positive samples both in cold and hot water were higher than other studies done worldwide (Dimitriadi and Velonakis, 2014;Khleifat et al, 2014;Leoni and Legnani, 2001;Stojek et al, 2012;Serrano-Suárez et al, 2013;Yarom et al, 2010). However, percentages of Legionella-positive samples reported in various studies are difficult to compare due to differences in the water systems, climate and environmental factors.…”
Section: Legionella In the Potable Water Systemmentioning
confidence: 71%
“…As described in our study the highest rate of Legionella colonization was detected in hot water networks of CB. In other European countries some slightly lower percentages of flat water networks colonization were obtained (12%) [ 13 , 29 ]. As detected in our study, the European data show some correlations between the Legionella growth in pipework and the presence of specific water physical-chemical parameters, as the temperature of 44–48 °C, the absence of chemical disinfection and the pH values around 7.9 [ 13 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%